Microclimatic Warming Leads to a Decrease in Species and Growth Form Diversity: Insights From a Tropical Alpine Grassland - Duchicela, Sisimac A.; Cuesta, Francisco; Tovar, Carolina; Muriel, Priscilla; Jaramillo, Ricardo; Salazar, Edison; Pinto, Esteban (Frontiers in Ecology and Evolution, 2021)
Due to warming, changes in microclimatic temperatures have shifted plant community structure and dynamics in tundra and alpine regions. The directionality and magnitude of these changes are less known for tropical alpine ecosystems. To understand the likely trajectory of these shifts in the Andes, we conducted a warming experiment in the northern Andes—using open-top chambers (OTC). In this study, we ask (1) how do OTCs affect air and soil temperatures in microclimates of tropical alpine regions, year-round and during the dry season? (2) What are the effects of seven years of warming on (a) the aboveground biomass (AGB) and (b) the plant taxonomic and growth form diversity? We installed five monitoring blocks in 2012 at ca. 4,200 m asl with 20 OTCs and 50 control plots randomly distributed within each block. We measured AGB, plant community diversity, and growth form diversity between 2014 and 2019. After seven years of warming, we found significant increases in mean monthly (+0.24 ºC), daily (+0.16 °C), and night air temperatures (+0.33 ºC) inside the OTCs, and the OTCs intensified microclimatic conditions during the dry season. Additionally, OTCs attenuated extreme temperatures—particularly in the soil—and the number of freezing events. AGB significantly increased in OTCs, and by 2019, it was 27% higher in OTCs than in control. These changes were driven mainly by a progressive increment of tussock grasses such as Calamagrostis intermedia, typical of lower elevations. The increase of tussocks led to a significant decrease in species diversity and evenness inside OTCs, but not in species richness after accounting by sampling time. Furthermore, cushions and herbs decreased inside OTCs. Our results show that experimental warming using OTCs in equatorial regions leads to decreased daily thermal amplitude and night temperatures rather than the level of increase in mean temperatures observed in temperate regions. The increase of tussocks and decrease in diversity of species and growth forms due to prolonged modifications in microclimatic temperature might be a step towards shrub-dominated ecosystems. Further research on this topic would help understand shifts in growth form dominance and the direction and rate of change of the system.